Pipe Surface Roughness at Microscale and Discussion of Possible Relation to Flow Properties - Qiao,Yiting; Kajbaf Nezhad,Mahsa (TVVR21/5014, 2021)
Despite decades of intense research, the behavior of water molecule still warrants new research.Water flow through various pipe systems has become a pivotal corner stone of functioning human infrastructure. the energy consumed by the pumping system takes the proportion ofaround 22% of the supplied energy for electromotors around the world (Shankar et al. 2016). A large amount of annual budget in each country is spent on pumping water through pipes. Minimizing the energy loss in the pipe and pumping systems is of great importance and interest.One important variable is the energy loss due to the friction at the boundary level near the pipewall, which could be strongly affected by the microstructure of the interior wall of the pipe and specific patterns how different pipe materials deteriorate with age. This project is an attempt tominimize energy loss during water transportation through pipes. We characterized microscalesurface texture of PVC and PE pipe inner surfaces and attempted to quantify energy loss dueto roughness of the inner surface of the pipe. We used Scanning Electron Microscopy (SEM) to obtain high resolution images of pipe surface that we further analysed with MountainsSEM. In the pipes we studied on average three to four million water molecules can fit in the distance between highest peak to valley of the surface topography. We studied 0.3 mm2of pipesurface for each sample. When this result is extrapolated across entire pipes surface totalenergy loos might be noticeable. However, this method has many flaws and further research program is necessary to give definitive answer.In this study three different pipes (sample (a) PVC diameter of 110 mm, sample (b) PE Diameter of 110 mm, and sample (c) PE diameter of 16 mm) were observed and analyzed by SEM,the roughness height were described by roughness parameter Rf, which were 142.2, 132.9and 123.4 micrometers respectively. This result means around 3 to 4 million water moleculescan fit in this height which can have hydrogen bonds within themselves, and solid wall. Dissociation bond energy for the HO is about 20.8 KJ/mole, and for the HC the value is almost 500KJ/mole. Considering friction loss is from the bonds between water molecules and wall, onlyone of the peaks can cause 3.36∙10L−15 KJ,2.84 ∙10L−15 KJ, 2.61∙10L−15 KJ extra energylost in sample a, b and c respectively. This is the result of increase in the solid surface that water molecule can make HC hydrogen bond with. With assumption of turbulent flow velocity of 1 m/s through a 100 meter long pipe, the friction factor calculated by Darcy-Weisbach equation of the three pipe samples were 0.0210, 0.0206 and 0.0340 correspondingly. To achieve a better resolution images of pipes interior, we suggest that in future it is more fruitful to use Atomic Force Microscope (AFM). To fully address the research question, it is necessary in future to track movements of a singe water molecule to precisely quantify how it creates andbreaks bonds with other molecules and move in the pipe. And finally one must remember that such studies in different ambient temperatures because temperature directly affects length ofthe water molecule bonds and through them the water flow energy. Darcy-Weisbach leanson simplified rough assumptions of temperature effects to calculate friction loss as kinematic viscosity. It is important to meticulously evaluate whether more detailed coefficients for these variables could help us to save energy to a meaningful level.
Keywords: pipe flow; roughness; microscale; SEM